Joint Effects of Dynamic Time Slot Scheduling Schemes and Soft Handoff on the Performance of TDD DS-CDMA Systems with 2D Rake Receivers - Pierre Fabris Hoefel, Roger; de Almeida, Celso (Journal of Communication and Information Systems, 2015)
In this paper, we derive analytical expressions to assess the performance of Time Division Duplexing (TDD) Direct Sequence-Code Division Multiple Access (DS-CDMA) systems with coherent bi-dimensional (2D) Rake receivers. Considering either hexagonal macrocellular and microcellular cross-shaped networks, we propose and evaluate different approaches to model the effects of the intercellular multiple access interference (MAl) on the performance of DS-CDMA systems with 2D Rake receivers. These results are then used on the performance comparison between coherent and optimum 2D Rake receivers. It is shown that soft handoff allows gains of 2 dB in the Signal-to-Interference-plus-Noise-Ratio (SINR) at the 2D Rake receiver output. Simulation results, ratified by theoretical upper bounds, show that the dynamic time slot allocation schemes allow considerable increase of the SINR at the receiver output with a concomitant improvement on the throughput.